Obfuscation for object‐oriented programs: dismantling instance methods. (4th April 2013) - Liaw, Heh‐Tyan; Wei, Shih‐Chieh
SUMMARY Code obfuscation can help software developers protect technological secrets. Code readability is greatly enhanced with object‐oriented technology that represents dynamic binding using instance method invocation. Therefore, dismantling instance methods is proposed in this paper as a critical obfuscating technique for object‐oriented programs. The interception classes are interpolated first into the project. The static images and the up forwarders are then created. For each virtual function system and each interface function system, a respective dispatching function is set up. By properly arranging the class identifiers and binding identifiers, the switch statement in the dispatching function can be compiled into constant‐time low‐level code. After using dispatching functions to simulate virtual function system or interface function system invocations, all original instance methods in the project will be removed. Interception functions and export functions are indispensable in supporting the operation of callback methods. A prototype of our obfuscation system was implemented and successfully tested on some practical scale applications. Copyright © 2013 John Wiley & Sons, Ltd.